Analysis on the Implementation of Public Policyy on Public Service Mall Program in Pamekasan Regency, East Java - Andi Ali Syahbana (Airlangga Development Journal, 2026)
Referring to the Law of the Republic of Indonesia Number 25 of 2009 concerning Public Services, it provides that public services are activities in the context of fulfilling service needs in accordance with laws and regulations for every citizen and resident of goods, services, and/or administrative services. provided by public service providers. One form of public service that is developing is the existence of internet- based public service innovations by utilizing information and communication technology in its implementation. One form of E-Government-based public service product in Pamekasan Regency is the Public Service Mall or MPP. This is in line with the mandate of Pamekasan Regent Regulation Number 20 of 2019 Article 1 Paragraph 8 explains that Public Service Malls are activities in the context of fulfilling services in accordance with the provisions of laws and regulations for citizen and resident of goods, services and/or administrative services provided by public service providers.